Repositioning AI in ELT: Supporting teachers in transforming English language evaluation - Fitria Lapele; Abel Yohanis Romrome; Eko Wahyunanto Prihono (Universitas Muhammadiyah Malang, 2026)
The rapid advancement of artificial intelligence (AI) has significantly transformed pedagogical and evaluative practices in higher education, yet its role in English language evaluation remains relatively underexplored. Previous studies predominantly examine general classroom applications or student perspectives, providing limited insight into how English teachers employ AI within evaluation practices. This study addresses this gap by investigating teachers’ perceptions of AI as a teaching assistant in English language evaluation. Employing a qualitative design, data were gathered through semi-structured interviews with seven English teachers, which were then analyzed thematically. The findings reveal four interrelated dimensions of AI-supported evaluation: (1) efficiency in evaluation design, (2) empowerment in formative and reflective practices, (3) ethical and valid use of AI, and (4) institutional readiness for sustainable integration. The study contributes new empirical evidence by showing how teachers actively negotiate the pedagogical, ethical, and policy-related challenges of integrating AI, an aspect often overlooked in earlier research. These insights highlight that AI functions most effectively as a collaborative partner that augments, rather than replaces, human evaluative judgment. The study offers both theoretical implications for AI-mediated evaluation literature and practical guidance for institutions seeking responsible and sustainable AI integration.